2019
DOI: 10.31580/jmi.v6i3.968
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Intentions of Different Genders of Different Religions: Purchasing Halal Logo Products at Convenience Stores in Hatyai

Abstract: Producers are investing to produce halal products. The halal product demand and importance has increased in recent years. The focus of the research, identifying behavioral intentions of different genders of different religions in respect of purchasing products bearing the halal logo at convenience stores in Hatyai. For collecting data 7-Eleven store chain was targeted. Theory of reasoned action (TRA) model was utilized as a conceptual model. Response collected through a structured survey instrument, using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 35 publications
0
28
0
1
Order By: Relevance
“…Armitage and Conner (2001) in their research, they adopted TPB as the basic conceptual model, along with new independent variable "Habit". (2002), Suh and Han (2003) and Jumani and Sukhabot (2019).…”
Section: Islamic Brands By Customermentioning
confidence: 99%
See 1 more Smart Citation
“…Armitage and Conner (2001) in their research, they adopted TPB as the basic conceptual model, along with new independent variable "Habit". (2002), Suh and Han (2003) and Jumani and Sukhabot (2019).…”
Section: Islamic Brands By Customermentioning
confidence: 99%
“…If the brand is produced or developed in the non-Muslim country, it may put an obstacle in the decision making for a Muslim. Because Muslims adopt those products, which are halal (Jumani and Siddiqui, 2012;Jumani et al, 2019). Because of this aspect, academician introduces the Islamic concept brands by country of origin.…”
Section: Islamic Brand/s By Country Of Originmentioning
confidence: 99%
“…A viable relationship persists between personal intrinsic religiosity and product knowledge with purchase intention of halal products for the Muslims (Nurhayati and Hendar, 2019), who seriously follow the halal logo (Jumani and Sukhabot, 2019). Practical implications for the marketers include capitalizing the extensive awareness on halal to tap marketing opportunities of halal cosmetics, as non-Muslim marketers have already entered in Bangladesh, but home-grown marketers are yet to appear.…”
Section: Implications Of the Findingsmentioning
confidence: 99%
“…Two studies by Verbeke et al (2004) and Honkanen et al (2005) have suggested that TPB should be used as a primary consumer research area model. Such as the TPB model used by Joey (2002, 2004); Sparks and Shepherd (1992), Jarvenpaa and Todd (1997); Maria et al (2001), Pavlou (2002); Anssi and Sanna (2005); Battarcherjee (2002), Suh and Han (2003); Jumani and Sukhabot (2019).…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…A TPB guidance identified by TPB founder Ajzen (1991) was used to design the current research instrument. In the current analysis, the attitude element is the Islamic brands’ attitude (Jumani and Sukhabot, 2019). This work takes only one aspect of the TPB attitude.…”
Section: Instrumentmentioning
confidence: 99%